Encyclopedia of food and culture - Katz, Solomon H., 1939-; Weaver, William Woys, 1947- (New York : Scribner, 2003)
"This stunning source explores the nutritional and cultural impact of food, with articles written by anthropologists, chefs, food historians, nutritionists, agronomists, food stylists, and other food researches. The well-written and informative entries cover the history of regional cuisines, major festivals and feasts, and general subjects that examine the cultural, sociological, and psychological perspectives of food. Encyclopedia of Food and Culture will be a classic for years to come."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.
Includes bibliographical references and index.
Keywords: Food habits -- Encyclopedias; Food -- Encyclopedias